Soil carbon sequestration, carbon markets, and conservation agriculture practices: A hypothetical examination in Mozambique - Timoteo E. Simone; Dayton M. Lambert; Ivan Cuvaca; Neal S. Eash (International Soil and Water Conservation Research, 2017)
Payments for Environmental Services (PES) are relatively novel mechanisms whereby the adoption of sustainable management practices by a stakeholder is rewarded by incentives linked to external markets. Adoption of PES for conservation agricultural practices (CAPS) by smallholder farmers may provide opportunities to increase household income or cover the technology costs of adoption if the carbon sequestration benefits of CAPS are quantifiable, adoption rates are accelerated and maintained, a mechanism exists whereby carbon sequestration services can be compensated, and carbon offset exchange markets are viable. This research suggests a methodology to examine a PES market for carbon offsets generated by the adoption of CAPS by farmers in Mozambique. Assuming a cumulative adoption of 60% over a 20-year period, revenue from PES market participation to CA adopters was two times higher than revenue earned when disadoption occurred midway through the simulation. Lower adoption targets are associated with higher per household returns when fertilizer rates typical to the region are increased. Establishing and maintaining a sustainable PES system in the study region would require significant investment in time and resources. The lack of on-the-ground institutions or local support for such a program would also challenge successful implementation. Finally, the programs where participant success depends on external markets, such as the hypothetical one suggested here, are subject to the ebb and flow of foreign demand for carbon offsets. Addressing these three broad constraints to a PES/CAPS program in the region would require grass-roots driven policy initiatives with buy-in at multiple social, economic, and political levels.